Mercury Export From Freshwater to Estuary: Carbocentric Science Elucidates the Fate of a Toxic Compound in Aquatic Boreal Environments - Demarty, Maud; Bilodeau, François; Tremblay, Alain (Frontiers in Environmental Science, 2021)
The chemistry of mercury in freshwater systems, particularly man-made reservoirs, has received a great deal of attention owing to the high toxicity of the most common organic form, methylmercury. Although methylmercury bioaccumulation in reservoirs and natural lakes has been extensively studied at all latitudes, the fate of the different forms of mercury (total vs. dissolved; organic vs. inorganic) along the entire river-estuary continuum is less well documented. In fact, the difficulty of integrating the numerous parameters involved in mercury speciation in such large study areas, combined with the technical difficulties in sampling and analyzing mercury, have undoubtedly hindered advances in the field. At the same time, carbocentric science has grown exponentially in the last 25 years, and the common fate of carbon and mercury in freshwater has become increasingly clear with time. This literature review, by presenting the knowledge acquired in these two fields, aims to better understand the extent of mercury export from boreal inland waters to estuaries and to investigate the possible downstream ecotoxicological impact of reservoir creation on mercury bioavailability to estuarine food webs and local communities.